Believe me ebook A novel. - Delaney, JP (2018)
In this twisty psychological thriller from the  New York Times  bestselling author of  The Girl Before,  an actress plays both sides of a murder investigation.   “[A] rich, nuanced, highly literary take on the  Gone Girl  theme.”— Booklist  (starred review)   Claire Wright is desperate. A British drama student in New York without a green card, she takes the only job she can get: working for a firm of divorce lawyers, posing as an easy pickup in hotel bars to entrap straying husbands. But then the game changes.    When one of her targets becomes the suspect in a murder investigation, the police ask Claire to use her acting chops to lure him into a confession. From the start, she questions the part she’s being asked to play: Is Patrick Fogler a killer? Or is there more to this setup than she’s being told?   Claire will soon realize she is playing the deadliest role of her life.    Praise for  Believe Me   “For readers who enjoyed the paranoia factor in A. J. Finn’s  The Woman in the Window  or the unreliable narrator of Paula Hawkins’s  The Girl on the Train .” — Library Journal   “Produces a bobsled run’s worth of twists.”  — Publishers Weekly   “An intense, stylish psychological thriller.” — Good Housekeeping   “A dark and haunting thriller . . . A superb evocation of conflicted emotions, this never lets you guess what’s coming next.” — Daily Mail   “I so enjoyed it—what a twisty, exciting read.” —Sabine Durrant, author of  Lie With Me